The Design and Qibla Direction by Using the Hmc 5883 L Sensor as a Compass Rhi in the UMSU Science Laboratory (OIF) - Sudirman Lubis; Faisal Irsan Pasaribu; Wawan Septiawan Damanik; Munawar Alfansury Siregar; Irpansyah Siregar; Edi Sarman Hasibuan (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
The level of accuracy of a measuring instrument is expected to be good because it is expected to provide information that can be used as a reference and benchmark in research and application in public life. The use of a compass measuring device in determining the direction of the wind and the location of the magned earth may vary from year to year such as the compass analog and digital. Both offer good reading results with the same way of working utilizing magnetic poles north and south as a reference point. HMC 5883L sensor is one measuring tool that is able to detect the direction of the compass with the same way of working from analog and digital compasses. By using Arduino Uno as a microcontroller as a central control that is able to change the information received from the HMC 5883L sensor into an easy-to-understand form of data. Qibla is more accurate by comparing the reading results of both. The results of the HMC 5883L compass sensor reading will be visualized in the form of the pointer, the pointer light and will be changed in numerical form. All data changed in the form of work is the result of an order from Arduino Uno received from the HMC 58883L sensor. A total of eight LED lights are used as a pointer to the compass and are connected with data obtained from the sensor.